Eco-Friendly Approach and Potential Biodegradable Polymer Matrix for WPC Composite Materials in Outdoor Application - Alessia Quitadamo; Valerie Massardier; Marco Valente (International Journal of Polymer Science)
Blends based on high-density polyethylene (HDPE) and poly(lactic) acid (PLA) with different ratios of both polymers were produced: a blend with equal amounts of HDPE and PLA, hence 50 wt.% each, proved to be a useful compromise, allowing a high amount of bioderived charge without this being too detrimental for mechanical properties and considering its possibility to biodegradation behaviour in outdoor application. In this way, an optimal blend suitable for producing a composite with cellulosic fillers is proposed. In the selected polymer blend, wood flour (WF) was added as a natural filler in the proportion of 20, 30, and 40 wt.%, considering as 100 the weight of the polymer blend matrix. There are two compatibilizers to modify both HDPE-PLA blend and wood-flour/polymer interfaces, i.e., polyethylene-grafted maleic anhydride and a random copolymer of ethylene and glycidyl methacrylate. The most suitable percentage of compatibilizer for HDPE-PLA blends appears to be 3 wt.%, which was selected also for use with wood flour. In order to evaluate properties of blends and composites tensile tests, scanning electron microscopy, differential scanning calorimetry, thermogravimetric analyses, and infrared spectroscopy have been performed. Wood flour seems to affect heavy blend behaviour in process production of material suggesting that future studies are needed to reduce defectiveness.